The value of x in the figure would be 14. Option 3.
To get x, we can use the following formula:
Sine 45 = opposite/hypotenuse
In this case:
opposite = 7√2
hypotenuse = x
Thus:
Sine 45 = 7√2/x
x = 7√2/sine 45
= 7√2/√2/2
= 7√2 x 2/√2
= 14
In other words, the value of x is 14.
More on trigonometry can be found here: brainly.com/question/14478957
#SPJ6
B. The value of g(-2) is the same as the value of g(4).
C. The values of g(-2) and g(4) cannot be compared.
D. The value of g(-2) is larger than the value of g(4).
Answer:
D. The value of g(-2) is larger than the value of g(4).
Step-by-step explanation:
Given : Given the function g(x) = -3x + 4, compare and contrast g(-2) and g(4).
To find : Choose the statement that is true concerning these two values.
Solution : We have given that
g(x) = -3x + 4
g (-2) = -3 ( -2) + 4.
g (-2) = 6 + 4
g (-2) = 10 .
Now,
g (4) = -3 ( 4) + 4.
g (4) = -12 +4 .
g (4) = -8.
g (-2) > g (4)
10 > -8 .
Therefore, D. The value of g(-2) is larger than the value of g(4).
A product of two (or more) factor can be zero if and only if at least one of the factors is zero.
In other words, you cannot multiply two non-zero real numbers, and have zero as a result.
So, if we want the product of these two factors to be zero, at least one of them has to be zero.
The first factor is zero if
The second factor is zero if
The solutions to the equation are x = 2 and x = -5.
To find the solutions to the equation (x – 2)(x + 5) = 0, you need to set each factor equal to zero and solve for x. When the product of two factors is equal to zero, one or both of the factors must be equal to zero.
Set x - 2 = 0 and solve for x:
x - 2 = 0
x = 2
Set x + 5 = 0 and solve for x:
x + 5 = 0
x = -5
The solutions to the equation are x = 2 and x = -5. When you substitute these values back into the original equation, you get (2 - 2)(2 + 5) = 0 and (-5 - 2)(-5 + 5) = 0, both of which evaluate to 0, confirming that these are indeed the solutions.
To know more about equation:
#SPJ6
Answer:
Step-by-step explanation:
We would apply the formula for determining compound interest which is expressed as
A = P(1 + r/n)^nt
Where
A = total amount in the account at the end of t years
r represents the interest rate.
n represents the periodic interval at which it was compounded.
P represents the principal or initial amount deposited
From the information given,
P = £600
r = 3.2% = 3.2/100 = 0.32
n = 1 because it was compounded once in a year.
t = 6 years
Therefore,.
A = 600(1 + 0.032/1)^1 × 6
A = 600(1.032)^6
A = £724.82